Brucellosis aortitis: An interesting case. Issue 2 (22nd January 2021) - Joghataie, Pegah; Salahi, Sarvenaz; Hosseini, Leila; Rezaeian, Nahid
Abstract: A 24‐year‐old woman referred to our radiology department with the diagnosis of new positive blood culture brucellosis and severe aortic regurgitation for evaluation of periaortic thickening. Cardiac magnetic resonance imaging elegantly revealed the presence of active aortitis, most probably caused by brucellosis.